Magnetic field dependence of conductivity and effective mass of carriers in a model of Mott-Hubbard material - Didukh, L.; Kramar, O.; Skorenkyy, Yu.; Dovhopyaty, Yu. (Condensed Matter Physics, 2005)
The effect of external magnetic field h on a static conductivity of MottHubbard material which is described by the model with correlated hopping of electrons has been investigated. By means of canonical transformation, the effective Hamiltonian is obtained which takes into account strong intra-site Coulomb repulsion and correlated hopping. Using a variant of generalized Hartree-Fock approximation the single-electron Green function and quasiparticle energy spectrum of the model have been calculated. The static conductivity σ has been calculated as a function of h, electron concentration n and temperature T . The correlated hopping is shown to cause the electron-hole asymmetry of transport properties of narrow band materials